MODEL PELAYANAN REHABILITASI SOSIAL ORANG DENGAN HIV DI INDONESIA - Moch Zaenal Hakim (Jurnal Ilmu Kesejahteraan Sosial HUMANITAS, 2019)
Problems faced by People Living With HIV (PLWH) not only health problems, but also social problems. Efforts to deal with PLWH are carried out through the social rehabilitation process. So far, social rehabilitation carried out by the Ministry of Social Affairs of the Republic of Indonesia towards PLWH is very limited. Overall, from 2009 to 2014, the Ministry of Social Affairs was only able to rehabilitate 160 people who were carried out through the ODH Social Rehabilitation Institution located in Sukabumi West Java. Thus, the services provided are far from expected. Therefore, to improve the quality and expansion of the range of services it is necessary to develop the Social Institution for PLWH Social Rehabilitation. This research was conducted to design a model of social rehabilitation services for PLWH in Indonesia. The study was conducted by examining the standards of public services and special services available at the Social Institution for PLWH Social Rehabilitation in Sukabumi. The method used research and development method. Data resource derived from social workers in social rehabilitation institution, Ministry of Social Affairs, The National AIDS Commission and Pelita Ilmu Jakarta Foundation. The result generally showed that Social Rehabilitation Institution for PLWH had common and specific standards, but still has limitation in human resources, basic social services and service range. Therefore it needs improvement various capacity, especially social workers both in quality and quantity.